The Acceptance of ATM Drive Thru of Bank CIMB Bintaro Branch Jakarta Using UTAUT Model - Normah Normah; Abdul Hadi; Fani Nurona Cahya (LPPM Universitas Bina Sarana Informatika, 2023)
Drive thru ATM Service is one application of technology in the field of banking services which allows customers to take money without leaving their car. With this Drive thru ATM service customers can take money easily and quickly. The objective of this research is to know how big the customer acceptance to the existence of this Drive thru ATM service by using research method of UTAUT model (Unified Theory of Acceptance and Use of Technology). This research uses 5 (five) constructs in UTAUT (Perified Expectancy), Effort Expectancy, and the intention of keprilakuan to use the system (Behavioral Intention to Use The System). With the implementation of this research has been known how much the acceptance of customers to the presence of Drive thru ATM service. The results showed that the use of Drive thru ATM service was welcomed by customers of Bank Cimb Niaga. Because there is a positive relationship between all the variables included in the study and all hypotheses have a good effect. So the conclusion is independent variables significantly have a positive relationship to the dependent variable